M&A deal initiation and managerial motivation - Fidrmuc, Jana P.; Xia, Chunling (Journal of Corporate Finance, 2019)
This paper contributes to our understanding of managers' motivations for initiating the sale of their company. Using a sample of 1098 publicly-listed US target firms with completed deals, we show that deals initiated by the target firm rather than by outside bidders have higher CEO ownership. Furthermore, CEOs are motivated to offer their firms for sale also by higher golden parachutes, stock and stock option grants prior to takeovers. Our results suggest that motivated CEOs participate actively in deal negotiations, rather than being bribed not to resist the deal. In target-initiated deal firms, CEO ownership and equity grants are also positively correlated with takeover premiums.